Vernacular Religion, Contemporary Spirituality and Emergent Identities: Lessons from Lauri Honko - Bowman, Marion (The Donner Institute, Åbo Akademi, 2014)
Marion Bowman is Senior Lecturer in Religious Studies at The Open University, UK. She is Vice-President of the European Association for the Study of Religions and a Director of The Folklore Society. Working at the interstices of religious studies and folklore, her research interests are very much rooted in vernacular religion and she has conducted a long-term ethnological study of Glastonbury. She is also interested in material culture, sacred space, contemporary Celtic spirituality, pilgrimage, airport chapels, spiritual economy, religion in Newfoundland and the creation of myth and tradition. Her latest book (co-edited with Ülo Valk) is Vernacular Religion in Everyday Life: Expressions of Belief (Equinox 2012). This article examines lessons which can still be learned from Professor Lauri Honko’s research and writings, particularly for those working at the interstices of folklore and religious studies who appreciate the mutually enriching relationship between the two fields which has been the hallmark of modern Finnish and Nordic scholarship. Three broad areas are considered here by way of illustration: the importance of studying belief and the continuing utility of genre as a tool of research; the use of folklore and material culture in the formation of cultural and spiritual identities in the contemporary milieu; and tradition ecology in relation to Celtic spirituality.